Training Teachers for the Organization of the Educational Work in the Mountainous Environment - Zavgorodnia, Tetiana (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
In the article, taking into account requirements to the teacher of higher educational establishment, contradictions which must be untied in the process of their professional preparation, the special accent is done on the ways of forming of the valued orientations, ideals of future teacher. The basis of necessity of reformation the preparation of specialists of the different industries, selection of the basic requirements to the teacher of modern HEE some ways of upgrading open up them psychologo-pedagogical preparation. Problems of forming for the junior schoolboys culture of the health, which level depends on the ecological cultureare examined in the article. The important constituent of culture of the health of the child is the level of her knowledge about an environment, formed of responsible attitude toward it, ability of it to keep and rationally use it in the everyday life.